Microbial Nanotechnology : Advances in Agriculture, Industry and Health Sectors (De Gruyter, 2022)
Applications of microbial nanotechnology are currently emerging with new areas being explored. Biosynthesis of nanomaterials by microorganisms is a recently attracting interest as a new, exciting approach towards the development of 'greener' nanomanufacturing compared to traditional chemical and physical approaches. This book will cover recent advances of microbial nanotechnology in agriculture, industry, and health sectors.